1996
DOI: 10.1037/0278-6133.15.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Role of the self-image and smoker stereotype in smoking onset during early adolescence: A longitudinal study.

Abstract: The present study utilized a longitudinal design to assess whether self-consistency or self-enhancement motives are predictive of future smoking onset. Participants were 1,222 nonsmoking 5th through 8th graders who were followed into the next academic year. The results showed that teens who were above the median in similarity between their self-image and smoker stereotype on coolness, sociability, and intelligence were almost twice as likely to show smoking onset at the 2nd measurement. This is supportive of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 12 publications
2
26
1
1
Order By: Relevance
“…One study demonstrated that many of the reasons given by Navy recruits about why they started smoking during their first year in the service were related to social image: “to show I wasn’t afraid,” “to want to be cool,” and “to look like an adult” (Cronan et al, 1991). Other studies have found that image-related attributions were consistently important for smoking across ages (Stanton & Silva, 1993), were more important among females than among males (Barton, Chassin, Presson, & Sherman, 1982), and predicted future cigarette smoking (Aloise-Young, Hennigan, & Graham, 1996). Consistent with previous findings in Western cultural contexts, this study indicates that Chinese adolescents perceived social image as an important reason for their smoking as well.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that many of the reasons given by Navy recruits about why they started smoking during their first year in the service were related to social image: “to show I wasn’t afraid,” “to want to be cool,” and “to look like an adult” (Cronan et al, 1991). Other studies have found that image-related attributions were consistently important for smoking across ages (Stanton & Silva, 1993), were more important among females than among males (Barton, Chassin, Presson, & Sherman, 1982), and predicted future cigarette smoking (Aloise-Young, Hennigan, & Graham, 1996). Consistent with previous findings in Western cultural contexts, this study indicates that Chinese adolescents perceived social image as an important reason for their smoking as well.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that smoking portrayals are consistent with adolescents' actual or ideal self images or a prototype of the ideal group member (that is, being cool), adolescents will be motivated to smoke to align self perceptions with personal ideals 2728 31 32 …”
Section: Discussionmentioning
confidence: 99%
“…Attribution research has been conducted to address cigarette smoking, a public health problem worldwide, among adolescents (Allbutt, Amos, & Cunningham-Burley, 1995; Aloise-Young, Hennigan, & Graham, 1996; Barton, Chassin, Presson, & Sherman, 1982; Cronan, Conway, & Kaszas, 1991; Kleinke, Staneski, & Meeker, 1983; McGee & Stanton, 1993; Rugkasa et al, 2001; Sarason, Mankowski, Peterson, & Dinh, 1992; Stanton, Mahalski, McGee, & Silva, 1993; Treacy et al, 2007). However, although previous attribution studies have identified self-reported cognitive attributions for smoking, they did not report whether those attributions were truly correlated with actual smoking behaviors, nor did they examine whether the attributions influenced future smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%